The Effect of Providing Boiler Ash as a Planting Medium on Plant Growth of Vegetative Seeds of Coconut Palm Oil (Elaeis guineensis Jacq.) in Pre-Nursery - M Andika Rifani; Ingrid Ovie Yosephine (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
Oil palm (Elaeis guineensis Jacq.) is a major plantation commodity that plays a strategic role in the national economy. Seedling quality during the nursery phase is a critical factor in determining the success of cultivating this crop. Boiler ash, a byproduct of oil palm shell and fiber combustion, contains macronutrients such as nitrogen, phosphorus, potassium, and magnesium and has the potential to improve the quality of the growing medium. This study aims to test the effectiveness of boiler ash as a component of the growing medium on the vegetative growth of oil palm seedlings during the early nursery or pre-nursery phase. The study location is at the Indonesian Palm Oil Technology Institute's Practice Garden. The study lasted for 3 months. The design used was a non-factorial Randomized Block Design (RBD) with 5 treatments: A0 (topsoil + sand), A1 (topsoil + sand + boiler ash 40 g), A2 (topsoil + sand + boiler ash 60 gr), A3 (topsoil + sand + boiler ash 80 gr), and A4 (topsoil + sand + boiler ash 100 gr). Each combination was repeated five times. The growth parameters measured included seedling height, stem diameter, number of leaves, and the fresh and dry weights of the upper part and the roots. Data were analyzed using chromatography. ANOVA was conducted at the 5% significance level. Boiler ash treatment at various levels did not show a significant effect (tn) on all observed growth parameters of pre-nursery phase oil palm seedlings. Although there was no significant effect, treatment A3 showed the highest seedling height value, namely 19.02 cm, while treatment A2 had the highest fresh shoot weight, namely 3.32 g. Overall, the results indicate that using boiler ash as a component of the growing medium during the pre-nursery phase does not significantly increase oil palm seedling growth. However, the advantages of this study provide scientific certainty for practitioners that the use of boiler ash at a dose of up to 100 grams per seedling is safe as a component of the growing medium, without causing toxic effects or inhibiting seedling growth in the early phase. As a recommendation, for users who want to utilize boiler ash waste optimally, it is recommended to apply it during the main nursery phase when seed nutrient reserves have been exhausted, or to combine it with organic materials that enrich other nutrients.